Identifying a critical window of maternal metal exposure for maternal and neonatal thyroid function in China: A cohort study. (June 2020) - Wang, Xu; Sun, Xian; Zhang, Yuqing; Chen, Minjian; Dehli Villanger, Gro; Aase, Heidi; Xia, Yankai
Highlights: The urinary detection rate of radioactive cesium in Chinese pregnant women is 100%. Mercury, cadmium and cesium may influence maternal and neonatal thyroid function. First trimester is a critical window for maternal metal exposure to thyroid function. Abstract: Background: China, a developing country, has a particularly serious problem with metal pollution. We evaluated the association of metal exposure during pregnancy with maternal and neonatal thyroid function, and identified the critical window for maternal metal exposure effects on maternal and neonatal thyroid functions. Methods: The maternal urinary concentrations of mercury (Hg), cadmium (Cd), arsenic (As) and cesium (Cs) were determined in pregnant women during their first (n = 389) or third (n = 257) trimesters in a prospective cohort from 2014 to 2015 in Nanjing, China, using an inductively coupled plasma mass spectrometry (ICP-MS) instrument. Maternal serum-free thyroxine (FT4) and thyroid-stimulating hormone (TSH) were measured by electrochemiluminescent microparticle immunoassays in the second and third trimesters. Neonatal TSH levels were detected 72 h after birth. Results: Hg (>0.162 µg/L), Cd (>0.084 µg/L), As (>0.348 µg/L) and Cs (>0.093 µg/L) were detectable in 76.9%, 90.1%, 100% and 100% of maternal urine samples from women in the first trimester of pregnancy. In the multiple adjusted linear regression models, maternal exposures to Hg and Cd in the first trimester were positively associated with maternal TSH levels in the second trimester ( P  < 0.01, P  = 0.02). Moreover, maternal exposures to Cd and Cs in the first trimester were positively associated with neonatal TSH levels ( P  = 0.04, P  = 0.02). In the Bayesian kernel machine regression (BKMR) model, the results were stable and consistent with the linear regression model. Conclusions: Maternal exposure to Hg, Cd and Cs in the first trimester was related to TSH levels in mothers and newborns. Efforts to identify maternal and neonatal thyroid disruptors should carefully consider the effects of exposure to these metals.